Pengaruh Karakteristik Pemerintah Daerah Terhadap Kinerja Pemerintah Daerah (Studi Pada Pemerintah Kabupaten/Kota di Provinsi Jambi) - Lia Anggraini; Sri Rahayu; Junaidi (Jurnal Akuntansi & Keuangan Unja, 2019)
ABSTRACT The purpose of this study is to provide empirical evidence of the influence of the characteristics of local governments on the performance of municipal / regency regional governments in Jambi Province. The population in this study were 11 districts / cities (9 districts and 2 cities) in Jambi Province in 2011-2015, the number of observations in this study was 55. The analytical method used was quantitative analysis, with panel data regression models using Eviews.10. The results of the study show: (1) The size of the local government does not affect the performance of the district / city government in Jambi Province. (2) The level of regional wealth has an effect on the performance of the district / city local government in Jambi Province. (3) Dependence on the Center has an effect on the performance of the district / city government in Jambi Province, (4) Capital expenditure Ratio does not affect the performance of the regency and city governments in Jambi Province, (5) Legislative Size does not affect the performance of district / city governments in Jambi Province, (6) Leverage does not affect the performance of district / city governments in Jambi Province (7) Size of regional government, level of regional wealth, dependence on the center, capital expenditure, legislative size, and leverage on Government performance Regency / City Region in Jambi Province. Keywords: Local Government Size, Regional Wealth Level, Dependence on Center, Capital Expenditures, Legislative Size, Leverge. ABSTRAK Penelitian bertujuan untuk memberikan bukti empiris pengaruh Karakteristik Pemerintah Daerah terhadap Kinerja Pemerintah Daerah kota/kabupaten di Provinsi Jambi. Populasi dalam penelitian ini adalah 11 kabupaten/kota (9 kabupaten dan 2 kota) pada Provinsi Jambi Tahun 2011-2015, jumlah pengamatan penelitian ini sebanyak 55. Metode analisis yang digunakan adalah analisis kuantitatif, dengan model regresi data panel dengan menggunakan Eviews.10. Hasil penelitian menunjukkan: (1) Ukuran pemerintah daerah tidak berpengaruh terhadap kinerja pemerintah daerah Kabupaten/Kota di Provinsi Jambi. (2) Tingkat kekayaan daerah berpengaruh terhadap kinerja pemerintah daerah Kabupaten/Kota di Provinsi Jambi. (3) Ketergantungan pada Pusat berpengaruh terhadap kinerja pemerintah daerah Kabupaten/Kota di Provinsi Jambi, (4) Rasio belanja modal tidak berpengaruh terhadap kinerja pemerintah daerah kabupaten dan kota di Provinsi Jambi, (5) Ukuran Legislatif tidak berpengaruh terhadap kinerja pemerintah daerah kabupaten/kota di Provinsi Jambi, (6) Leverage tidak berpengaruh terhadap kinerja pemerintah daerah Kabupaten/Kota di Provinsi Jambi.(7) Ukuran pemerintah daerah, tingkat kekayaan daerah, ketergantungan pada pusat ,belanja modal, ukuran legislative, dan Leverage berpengaruh terhadap kinerja Pemerintah Daerah Kabupaten/Kota di Provinsi Jambi. Kata Kunci: Ukuran Pemerintah Daerah, Tingkat Kekayaan Daerah, Ketergantungan pada Pusat, Rasio Belanja Modal, Ukuran Legislatif, Leverge.